Investigation of UCH-L1 levels in ischemic stroke, intracranial hemorrhage and metabolic disorder induced impaired consciousness - Yigit, Ihsan; Atescelik, Metin; Yilmaz, Mustafa; Goktekin, Mehmet Cagri; Gurger, Mehtap; Ilhan, Nevin (W B Saunders Co-Elsevier Inc, 2017)
Objective: We aimed to determine the levels of ubiquitin C-terminal hydrolase-L1 (UCH-L1) in patients admitted to the emergency department with impaired consciousness due to metabolic or neurological reasons. Materials - methods: The study included 80 patients with ischemic stroke (IS), 40 patients with intracranial hemorrhage (ICH), 80 patients with metabolic disorder induced impaired consciousness (MDIC) and 40 healthy controls. Results: The levels of UCH-L1 [median (IQR)] were as follows: 5.59 ng/mL (3.90-9.37) in IS, 5.44 ng/ml (4.01-13.98) in ICH, 3.34 ng/ml (2.29-5.88) in MDIC and 3.94 ng/ml (3.31-7.95) in healthy volunteers. Significantly higher levels were detected in IS and ICH than in MDIC and healthy volunteers. In ROC curve analysis, we detected 63.75% sensitivity and 62.5% specificity (AUC = 0.626, p < 0.0199, 95% CI: 0.533-0.713) with a cutoff value of 4.336 ng/ml for IS and 75% sensitivity and 55% specificity (AUC = 0.664, p < 0.0071, 95% CI: 0.549-0.766) with a cut-off value of 4.036 ng/ml for ICH. However, the sensitivity and specificity for MDIC was 36.25% and 77.5%, respectively, with a cut-off value of 3.256 ng/ml (AUC = 0.525, p = 0.6521, 95% CI: 0.432-0.617). UCH-L1 levels were found to increase significantly with increasing time between the onset of symptoms and blood sampling (r = 0.345, p < 0.001). However, no correlation was found between UCH-L1 levels and age (r = 0.014, p = 0.833), GCS (r = -0.115, p = 0.074), mRS (r = 0.063, p = 0.475) and NIHSS (r = 0.056, p = 0.520). Conclusion: In this study, we detected significantly higher levels of UCH-L1 in patients with IS and ICH compared to patients with MDIC and healthy volunteers. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Intracranial hemorrhage; Ischemic stroke; Ubiquitin C-terminal hydrolase-L1; Metabolic disorder induced impaired consciousness